Land use planning of the Bara tract area under Sardar Sarovar Canal Command of Gujarat - Chinchmalatpure, Anil R; Nayak, A K; Rao, G Gururaja (Indian Farming, 2015)
Productivity of the salt-affected black soils of the Bara tract area is not fully utilized because of raditional cultivation. The major soils of Bara tract are deep black clayey soils with montmorrillonite as dominant clay mineral with high water holding capacity. These soils have significant concentration of soluble salts in sub-soils, although the concentration in the surface layer is low. It was found that 40% of surface soils are free from salinity (